A comparative study on antioxidant activity and biochemical profile of exotic cocoa (Theobroma cacao L.) clones - Amudhan, M. Senthil; Apshara, Elain (Journal of Plantation Crops, 2015)
Please see the pdf file here: http://indsocplantationcrops.in/journal.php#